Goals, beliefs, knowledge, and barriers for diabetes selfcare in a multi-ethnic population in malaysia: A qualitative study - Neblett, Robert Saunders; Chia, Yook Chin; Abdullah, Nurdiana; Ablah, Elizabeth (Malaysian Medical Association, 2019)
Introduction: Ethnic differences may influence diabetes selfcare practices and glycaemic control among people with type 2 diabetes mellitus. This qualitative study explored goals, beliefs about treatment effectiveness, knowledge, and barriers to and facilitators for diabetes self-care among the three main ethnic groups in Malaysia. Methods: Patient focus group discussions were conducted in three different ethnic groups: Malays, Chinese, and Indians. Participants were recruited from the primary-care clinic of a university medical centre located in an urban area. Focus group discussions were audio-recorded, transcribed, and analysed using a thematic approach. Results: A total of 31 patients participated in the study: Malays (n=12), Indians (n=10), and Chinese (n=9). There were three sessions for each ethnic group. Reported goals primarily related to quality of life and glycaemic control. Participants expressed the belief that the combination of diet, exercise, and medications is effective for controlling diabetes. Groups described their obtaining information external to a healthcare system and reported a need for more specific, practical counselling from health professionals on diet, exercise, and medications. Barriers to and facilitators for diabetes self-care practices were categorised into three major themes: having discipline, social habits, and “other” themes. Conclusion: Emerging themes were similar across the ethnic groups and included quality-of-life goals, confidence in combination treatment, common use of complementary and alternative medicine, need for further counselling, and the challenge regarding self-discipline. © 2019, Malaysian Medical Association. All rights reserved.